Effects of long soil surface residence times on apparent cosmogenic nuclide denudation rates and burial ages in the Cradle of Humankind, South Africa. Issue 15 (13th September 2019) - Makhubela, T.V.; Kramers, J.D.; Scherler, D.; Wittmann, H.; Dirks, P.H.G.M.; Winkler, S.R.
Abstract: In situ cosmogenic nuclides are an important tool for quantifying landscape evolution and dating fossil‐bearing deposits in the Cradle of Humankind (CoH), South Africa. This technique mainly employs cosmogenic 10‐Beryllium ( 10 Be) in river sediments to estimate denudation rates and the ratio of 26‐Aluminium ( 26 Al) to 10 Be ( 26 Al/ 10 Be), to constrain ages of sediment burial. Here, we use 10 Be and 26 Al concentrations in bedrock and soil above the Rising Star Cave (the discovery site of Homo naledi ) to constrain the denudation rate and the exposure history of soil on the surface. Apparent 10 Be‐derived denudation rates obtained from pebble‐ to cobble‐sized clasts and coarse‐sand in soil (on average 3.59 ± 0.27 m/Ma and 3.05 ± 0.25 m/Ma, respectively) are 2‐3 times lower than the bedrock denudation rates (on average 9.46 ± 0.68 m/Ma). In addition, soil samples yield an average 26 Al/ 10 Be ratio (5.12 ± 0.27) that is significantly lower than the surface production ratio of 6.75, which suggests complex exposure histories. These results are consistent with prolonged surface residence of up to 1.5 Ma in vertically mixed soils that are up to 3 m thick. We conclude that the 10 Be concentrations accumulated in soils during the long near‐surface residence times can potentially cause underestimation of single‐nuclide ( 10 Be) catchment‐wide denudation rates in the CoH. Further, burial ages of cave sediment samples that consist of an amalgamation of sand‐size quartz grains could be overestimated if a pre‐burial 26 Al/ 10 Be ratio calculated from the surface production is assumed. © 2019 John Wiley & Sons, Ltd. Abstract : Using in situ 10 Be and 26 Al in bedrock, clasts and soil, we show that quartz in the soil has prolonged near‐surface residence times up to 1.5 Ma, leading to increased accumulation of cosmogenic nuclides and complex exposure histories. As a result, the catchment‐wide denudation rates are underestimated and the burial ages of fossil‐bearing deposits are overestimated.